STREET VENDORS EXTERNALITIES - -, Sutarjo (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2016)
There are externalities as a result of street vendors economic activities. The externalities may be negatives and may be positives.The method used to collect data through literature and the data collected is secondary data from reports and research publication. Negative externalities caused by the street vendors are accessibility of public spaces, garbage, open space inharmony, dirty and untidy, traffic congestion, pedestrian interference and the possibility of diseases due to lack of sanitation. Tragedy of the commons happened due to excessive uses of public facilities resulting in reduced or loss of its function. The Positive externalities are generate jobs, as a distributor, security, bring the servicecloser to the customers and means of recreation. In the newinstitutional economic point of view, the government needs to intervene as a governing body to avoid the tragedy of the commons over excessive use of public resources in the form of an open area which supposed to be able to be utilised by the society.